A quantified fidelity criterion for parameter-embedded watermarking of audio archives - Gurijala, A. R.; Deller, J. R. (Digital Libraries: 2003 Joint Conference On, 2003)
A novel algorithm for speech watermarking through parametric modeling is enhanced by inclusion of a quantified fidelity criterion. Watermarking is effected through solution of a set-membership filtering (SMF) problem, subject to an l∞ fidelity criterion in the signal space. The SMF approach provides flexibility in obtaining watermark solutions that trade-off watermark robustness and stegosignal fidelity.